Sovereign wealth funds as special international investors under global financial downfall - N. Drozd (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
An overview of origin, functional orientation and characteristics of sovereign wealth funds is presented. Possibility and necessity of cooperation between Ukraine and such systemic investors is proven.